OPTIMALISASI WISATA BUDAYA BATIK DI KAMPUNG CIKADU, TANJUNG LESUNG - Sembiring, Evi Dora; Sulistiawati, Deti; Pertiwi, Sari Putri (Batara Wisnu : Indonesian Journal of Community Services, 2022)
Cikadu Village is located in Tanjungjaya Village, Pandeglang, Banten–about eight kilometers from Tanjung Lesung beach. This Ciakdu Tourism Village is a relocation from several villages including Kalica, Cadasngampar, Cisadang, and Bodur villages. This village has natural and cultural beauty. Cikadu Village is one of the villages in the National Tourism Strategic Area (KSPN), which was directly appointed by the President of the Republic of Indonesia Joko Widodo to serve as a Tourism Village. One of the products produced by this village is batik. The majority of batik activities in Cikadu village are carried out by mothers who still use manual or traditional methods, which require patience and high accuracy. The implementation process is also very long, it can take 1 week or even 1 month depending on the motifs and colors used. One of the community service activities (PKM) sponsored by IDRI (Republic of Indonesia Lecturers Association) is a batik cultural tourism, namely knowing and learning the process of making batik manually. The method of activity carried out is by listening to the methods and techniques of batik which then immediately tries to practice how the batik process is. The expected result is that batik culture can continue to be preserved by wearing batik clothes or products and encourage batik activities which are a tourism attraction as one of Indonesia's cultural heritage